2006
DOI: 10.3109/2000-1967-059
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Pancreatic Portal Fistula as a Complication of Chronic Pancreatitis

Abstract: In this study we describe an unusual complication in a patient suffering from chronic calcifying pancreatitis. The patient had a fistula between the common bile duct, the pancreatic duct, and the portal vein. He received supportive medical treatment and achieved long-term survival. A review of the literature including diagnosis, treatment and outcome of this rare complication is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The pathogenesis of the present panceaticobiliary fistuli- (17). There has been mmo n b i l e d u c t ( l o n g a r r o w) , ma i n p a n c r e a t i c d u c t ( s h o r t a r r o w) , p a n c r e a t i c o b i l i a r y f i s t u l a ( a r r o wh e a d ) , n a r r o wi n g o f t h e ma i n p a n c r e a t i …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of the present panceaticobiliary fistuli- (17). There has been mmo n b i l e d u c t ( l o n g a r r o w) , ma i n p a n c r e a t i c d u c t ( s h o r t a r r o w) , p a n c r e a t i c o b i l i a r y f i s t u l a ( a r r o wh e a d ) , n a r r o wi n g o f t h e ma i n p a n c r e a t i …”
Section: Discussionmentioning
confidence: 99%
“…Pancreaticobiliary fistula is a rare condition generally associated with pancreatic pseudocysts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), acute necrotizing pancreatitis (19,20), pancreatic abscesses (21,22), and intraductal papillary-mucinous pancreatic neoplasm (IPMN) (23)(24)(25). This pathological condition generally presents symptoms such as hemobilia or obstructive jaundice soon after fistulous formation, or is found pathologically after operation on pancreatic pseudocysts caused by acute pancreatitis (13 …”
Section: Introductionmentioning
confidence: 99%
“…PPVF formation is a rare complication of pancreatitis which is reported more commonly in men than in women, and the etiology of the contributing pancreatitis is almost always alcohol-related. [ 4 ] No clear consensus on the mechanism for the formation of the fistulous tract has been reached, and there are diverging theories of the temporality of fistula formation and associated portal venous thrombosis, which is usually present. [ 4 ] Some authors suggested that the primary pathogenesis is related to the portal vein thrombosis acting as nidus for fistula formation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] While pseudocyst formation, portal vein thrombosis and arterial pseudoaneurysms are relatively well described and routinely diagnosed complications of pancreatitis occurring in up to 20% of the cases, the formation of a pancreatic-portal vein fistula (PPVF), in which a fistulous tract develops between the portal vein and pancreatic duct, is an extremely rare entity with only 18 cases reported in the literature till date. [ 2 3 4 ] In this report, we present a patient with recurrent episodes of acute pancreatitis due to a hereditary mutation in PRSS1, complicated by the development of a PPVF. This case study presents a diagnostic approach based on clinical, laboratory, and imaging characteristics, as well as shed some light on the response to therapy and disease evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreaticobiliary fistula is a rare pathological condition caused by pancreatic pseudocysts [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], acute necrotizing pancreatitis [19,20], pancreatic abscesses [21,22], and intraductal papillary-mucinous pancreatic neoplasm (IPMN) [23][24][25]. Most cases of pancreaticobiliary fistula are found because of an internal hemorrhage in pancreatic pseudocysts [13] or obstructive jaundice by IPMN [24].…”
Section: Introductionmentioning
confidence: 99%